Reframing Agricultural Extension in Urban Sustainability: The Role of Extension Agents in Strengthening Women-Led Urban Farming Institutions - Unang; Hartoyo, Tedi (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study examines how agricultural extension contributes to institutional development in a women-led urban farming group, using KWT Sahabat Sampah in Bekasi City as a case study. The group integrates waste management and hydroponic vegetable production, illustrating an emerging model of community-based urban sustainability. A descriptive quantitative approach was employed, with all 35 members participating through census sampling. Data were collected via structured questionnaires, field observation, and interviews with the assigned extension agent. Results indicate that extension support was consistently rated high across six dimensions, particularly facilitation. Institutional development indicators were likewise strong, though economic sustainability remains constrained. Spearman’s rank correlation (ρ = 0.678, p < 0.01) shows a substantial association between extension intensity and institutional development. These findings suggest that participatory, context-sensitive extension approaches are well-suited to urban settings and can strengthen women’s organizations as local sustainability actors.